“Destroyer and Teacher”: Managing the Masses During the 1918–1919 Influenza Pandemic - Tomes, Nancy (Association of Schools of Public Health, 2010)
The Spanish influenza arrived in the United States at a time when new forms of mass transportation, mass media, mass consumption, and mass warfare had vastly expanded the public places in which communicable diseases could spread. Faced with a deadly “crowd” disease, public health authorities tried to implement social-distancing measures at an unprecedented level of intensity. Recent historical work suggests that the early and sustained imposition of gathering bans, school closures, and other social-distancing measures significantly reduced mortality rates during the 1918–1919 epidemics. This finding makes it all the more important to understand the sources of resistance to such measures, especially since social-distancing measures remain a vital tool in managing the current H1N1 influenza pandemic. To that end, this historical analysis revisits the public health lessons learned during the 1918–1919 pandemic and reflects on their relevance for the present.